Podejście procesowe w zarządzaniu innowacjami - Prudzienica, Maja (A Process Approach in Managing Innovations, 2009)
The aim of the paper is to demonstrate the importance of undertaking creative activities by companies - activities that lead to introducing market and technological innovations as well as innovation management. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 52, s. 90-96